The Strategy of Inclusion of IKN News in kompas.com: Theo Van Leeuwen's Approach - Diah Ayu Lestari; Hermaliza (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The relocation of Indonesia's capital city from Jakarta to East Kalimantan has been studied by the government for many years. The move aims to accelerate economic equality, reduce the gap between Java and other regions, and support more inclusive economic growth. This research aims to examine the inclusion strategies used to see how the media presents various social actors in the news, as well as how they influence the narratives formed. This study uses a qualitative research approach in the form of a critical discourse analysis method with Theo Van Leeuwen's model, in order to identify how the media tries to create inclusive news and how media discourse can influence public perception of the issue. This research is considered significant because it is a novelty that provides a deeper understanding of how major media in Indonesia deal with major and controversial issues, as well as how they manage news coverage to ensure diversity of voices and balanced information in the digital realm. The results of the analysis show that there are 34 data from 25 news articles that use six inclusion strategies consisting of objectivation (8 data), nomination (6 data), determination (3 data), identification (3 data), individualization (10 data) and association (4 data). And there are strategies that are not found, namely differentiation, indifference, abstraction, categorization, identification, assimilation, and dissociation